2019
DOI: 10.1038/s41598-018-37502-w
|View full text |Cite
|
Sign up to set email alerts
|

New insights into culture negative endophthalmitis by unbiased next generation sequencing

Abstract: The proof-of-concept, study to investigate the presence of microorganisms in presumed infectious endophthalmitis using Next generation sequencing (NGS) was carried out in vitreous biopsies from 34 patients with endophthalmitis, and thirty patients undergoing surgery for non-infectious retinal disorders as controls. Following DNA extraction using the Qiagen mini kit and PCR amplification of the V3–V4 regions of the bacterial 16S rRNA and ITS 2 region of fungus, they samples were sequenced on an Illumina HiSeq 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 13 publications
4
51
0
1
Order By: Relevance
“…The use of NGS for infectious disease diagnostics is being increasingly explored and adopted for select applications in the clinical laboratory (4,(7)(8)(9)(10)(11)(12). Several approaches to pathogen detection with NGS can be undertaken (Table 2).…”
Section: Ngs For Infectious Disease Diagnosticsmentioning
confidence: 99%
“…The use of NGS for infectious disease diagnostics is being increasingly explored and adopted for select applications in the clinical laboratory (4,(7)(8)(9)(10)(11)(12). Several approaches to pathogen detection with NGS can be undertaken (Table 2).…”
Section: Ngs For Infectious Disease Diagnosticsmentioning
confidence: 99%
“…To cross the divide between the conventional microbiological methods and whole-genome sequencing, a culture free platform using targeted HTS would be an excellent, less complicated approach, with a lower cost to detect pathogens for implementation in diagnostic laboratories. We have previously shown that NGS is a good tool for microbial research in endophthalmitis [9], but the next big challenges will be the standardization and validation of procedures and bioinformatics pipeline that address the specific challenges for clinical standards, especially in culture-negative cases. HTS is more likely to become a future diagnostic tool in routine ocular microbiological laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the use of next-generation sequencing (NGS) has proven to be a promising diagnostic strategy for multiple detections of common and rare microorganisms, including virus associated with infectious uveitis and endophthalmitis present in single vitreous samples. An important contribution of NGS so far is related to the improvement of pathogen detection in cases of negative culture endophthalmitis [8].…”
Section: Advances In Diagnosis Of Uveitismentioning
confidence: 99%